Patients’ perceptions of self-administered dosing to opioid agonist treatment and other changes during the COVID-19 pandemic: a qualitative study - Luke Mitcheson; John Marsden; Natalie Lowry; Mike Kelleher; Gemma Scott; Sophie Turner; Annette Hodge; Waniya Ashraf; Katie McClean (BMJ Open, 2023)
Objectives During the COVID-19 pandemic, addiction treatment services received official guidance asking them to limit face-to-face contact with patients and to prescribe opioid agonist treatment (OAT) medication flexibly. With the aim for most patients to receive take-home supplies for self-administration rather than attendance for observed daily dosing.Design This was a theory-driven, clinically applied qualitative study, with data for thematic analysis collected by semi-structured, audio-recorded, telephone interviews.Participants Twenty-seven adults (aged ≥18 years) enrolled in sublingual (tablet) buprenorphine and oral (liquid) methadone OAT.Setting Community addictions centre in the London Borough of Lambeth operated by South London and Maudsley NHS Trust.Results Three major themes were identified: (1) dissatisfaction and perceived stigma with OAT medication dispensing arrangements before the pandemic; (2) positive adaptations in response to COVID-19 by services; (3) participants recommended that, according to preference and evidence of adherence, OAT should be personalised to offer increasing medication supplies for self-administration from as early as 7 days after commencement of maintenance prescribing.Conclusions In an applied qualitative study of patients enrolled in OAT during the COVID-19 pandemic, participants endorsed their opportunity to take medication themselves at home and with virtual addiction support. Most patients described a preference for self-administration with increased dispensing supplies, from as early as 7 days into maintenance treatment, if they could demonstrate adherence to their prescription.